Nurul daughter of tailor recipient of Telekom Excellence Award - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 17 March 2020 - Her mother’s tenacity and perseverance became the driving force and inspiration for Nurul Md Yunus, 26, who was selected to receive the Telekom Malaysia Berhad Excellence Award at the Universiti Malaysia Pahang (UMP) 15th Convocation Ceremony recently.